Utilizing the Shopee Marketplace Platform to Oprimize MSMEs Business Strategies in the International Digital Economy - Febima, Mesi; Asfi, Marsani; Lukita, Chandra; Magdalena, Lena; Hatta, Muhammad; Fahrudin, Rifqi; Chritviona Parera, Shalom; Winurcahyono, Alexander; Anggara Putra, Dwi Pasha; Nakeisha Wahyudi, Nayla; Mita, Shella (Jurnal Masyarakat Indonesia (Jumas), 2025)
This International Community Service activity is a collaboration between Catur Insan Cendekia University (UCIC) Cirebon, UNIKOM Bandung, the Department of Cooperatives, Small, Medium Enterprises, Trade and Industry (DKUKMPP) Cirebon City, and the African Institute for Multidisciplinary Studies (AIMS) Somalia, with the title 'Utilizing the Shopee Marketplace Platform to Oprimize MSMEs Business Strategies in the International Digital Economy'. This International Community Service activity aims to empower Micro, Small and Medium Enterprises (MSMEs) in optimizing business strategies in the era of the global digital economy through the use of the Shopee Marketplace platform. This activity includes a series of training and assistance for MSME players in understanding Shopee Marketplace features, branding optimization, inventory management, and data-based sales performance analysis. Apart from that, export strategies were provided using Shopee to reach international markets. In implementation, a hybrid approach was used, involving online sessions for participants from Somalia and offline sessions for participants in Cirebon City. The results of this activity showed a significant increase in participants' understanding regarding the use of digital platforms to increase product visibility and competitiveness in the global market. This activity makes a real contribution to empowering MSMEs in facing the challenges of globalization in the digital economy. This international collaboration is a relevant model in developing cross-institutional synergy to support MSMEs in a sustainable manner, especially in the midst of continuously developing digital transformation.